On the value of crowding in public transport for Île-de-France - Eric Kroes; Marco Kouwenhoven; Laurence Debrincat; Nicolas Pauget (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Since the mid 90's, public transport patronage in Île-de-France (the Paris region) has increased substantially: over the last decade alone a 20% growth was observed. This growth, even though it was an aim of the Sustainable Urban Mobility plan adopted in 2000, was not completely anticipated. Consequently, the capacity is no longer sufficient to meet the demand during the peak hours, particularly on several parts of the network in the dense central area of the region. This results in over-crowded vehicles and long waiting times for passengers at rail platforms and bus stops. The lack of maintenance and modernisation of the transport system causes additional operational difficulties. Renewal of the rail infrastructure and rolling stock is necessary to cope with this situation. But renewal alone will not be enough. Major investments are planned to increase capacity by either building new lines, or by increasing capacity of existing lines. The Grand Paris Express is the best known of these projects. Furthermore, a number of bus lines will be transformed into tramway lines, railway lines are being renovated, and new automatic systems for railway operation will allow shorter headways between subsequent trains, and thus more capacity. All these projects together should reduce the shortage of capacity substantially by 2020, and totally eliminate it by 2030. As a consequence, crowding levels in public transport will be highly reduced. For the socio-economic appraisal, it is necessary to quantify all impacts of these investments. The impact on travel and waiting times can be determined by using standard traffic models, such as the ANTONIN model that is used in the Île-de-France area. The reduction in congestion levels can also be forecasted by more using advanced traffic models. However, little is known about the value that passengers attach to these reduced congestion levels (for a review of existing literature, see section 3). Therefore, STIF commissioned Significance in 2011 to conduct a new study focused on the perception of comfort inside public transport vehicles in general, and more particularly on the issue of crowding. This study was to cover all modes of public transport in Île-de-France.
Keywords: 330